Growth, Characterization and Simulation of InAs Quantum Wires on Vicinal Substrates - Scullion, Andrew (My University, 2014)
The heteroepitaxial growth of InAs self-assembled quantum wires on vicinal substrates is investigated. InGaAlAs lattice-matched to InP was first deposited onto an InP(001) substrate with and without a 0.9 degree off-cut toward the (110) direction, followed by the deposition of a strained layer of InAs. Dense InAs quantum wires were successfully grown on both nominally flat and vicinal substrates in order to observe the effect of the presence of atomic steps. The off-cut angle was chosen based on the wire spacing on a flat substrate to serve as a template for their nucleation and improve their size distribution for use as 1.55 um wavelength lasers required by the telecommunications industry. The results have shown a modest but statistically significant improvement in the width of their size distribution. In addition, a kinetic Monte Carlo simulation including full strain calculations was developed to further understand the nucleation process. The model developed here disproves the idea that InAs quantum wires are aligned towards the (-110) direction due to diffusion anisotropy. The simulation of the formation of quantum wires similar to those observed experimentally has been achieved and the Stranski-Krastanow growth mode is demonstrated.
Keywords: quantum wires; heteroepitaxy; vicinal; off-cut; kinetic Monte Carlo; simulation; Semiconductor and Optical Materials; Semiconductor and Optical Materials